EFEKTIVITAS PROSES PENGOLAHAN PADA DEPOT AIR MINUM DI KABUPATEN BUTON TENGAH - Fitra, Ramad Arya Fitra Arya (Program Studi Kesehatan dan Keselamatan Kerja, 2019)
Water is a chemical compound that has a very important role in the survival of humans and other living things, especially for needs as drinking water. Therefore, before being made as drinking water it needs to be processed to reduce the level of pollution to a safe level. One way is through drinking water depots. The results of this study concluded that drinking water depots in Central Buton District that the results of location observations carried out on 12 depots in the field were 83.33% effective and 16.66% refill depots were ineffective. The building assessment carried out at 12 refill depots in Central Buton District obtained 83.33% and 16.66% refill depots. Testing of raw water carried out on 12 depots was obtained 100% did not meet the criteria for production water. Production water at 12 refill depots in Central Buton District was 58.33% and those that met the effective criteria and 41.66% were included in the ineffective criteria. In terms of washing and writing gallons to consumers obtained 75% data and 25% refill depots that fall into the ineffective category. More about the yard that 58.33% and the remaining 41.66% refill depots included in the ineffective category.